2016
DOI: 10.1177/0954008316675208
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of cyanate ester resin modified with acid-treated multiwalled carbon nanotubes

Abstract: Multiwalled carbon nanotubes (MWCNTs) that were treated with mixed acids were used to reinforce the cyanate ester resin. Meanwhile, the relationship among structure, morphology, and property of the modified resin was investigated. The treated MWCNTs were characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis, and X-ray photoelectron spectroscopy (XPS). The XPS results showed that the oxygen content in the treated MWCNTs was higher than that of untreated MWCNTs and the FTIR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…All of the initial decomposition temperatures of the BT resin were above 420°C, which were higher than the data in Li’s report. 8 In addition, the char yield at 600°C of cured modified CE is above 59%, and the char yield at 800°C is above 52%, which are quite high compared with the char yield at 600°C in the resin blends in Toldy et al’s research. 11…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the initial decomposition temperatures of the BT resin were above 420°C, which were higher than the data in Li’s report. 8 In addition, the char yield at 600°C of cured modified CE is above 59%, and the char yield at 800°C is above 52%, which are quite high compared with the char yield at 600°C in the resin blends in Toldy et al’s research. 11…”
Section: Resultsmentioning
confidence: 99%
“…However, a CE, as the resin matrix of a composite material, usually needs to be modified. 8,9 The toughness of a CE resin is so poor that the fracture toughness and inter-laminar shear strength (ILSS) of the composite materials usually cannot meet the requirements of the application. Common CE modification methods include thermosetting resin modification, thermoplastic resin modification and elastic modification.…”
Section: Introductionmentioning
confidence: 99%
“…fillers/fibers) after surface modifications. 29 Therefore, the aim of carrying out the FTIR analysis was to demonstrate the existence of the experimental additives on the hybrid fiber external surfaces. By carefully scrutinizing the IR absorption spectra, given in the inset of Figure 4, of the SKFs as well as SGFs before and after being surface modified, one can easily identify the presence of some additional bands in the studied wavelength range from 4000 cm À1 to 500 cm À1 .…”
Section: Surface Modification Of the Hybrid Fibersmentioning
confidence: 99%
“…Among the thermosetting resins, cyanate ester (CE) resin is highly suitable for the improvement of the thermal resistance of EP resin because the CE resin after cure has prominent heat resistance, low moisture absorption, and excellent dielectric properties. 7 9 There are many publications conducted on the compound of CE and EP aiming to integrate the superiorities over these two thermosetting resins. For example, Kim prepared EP/CE blends with a curing agent, 4,4′-diaminodiphenylsulfone, and found that the initial degradation temperature (the temperature at 5% weight loss) of the cured blend was shifted to higher temperatures with an increase in the CE resin content.…”
Section: Introductionmentioning
confidence: 99%